STRATEGI KOMUNIKASI KEPALA SEKSI PELAYANAN DALAM PELAYANAN PUBLIK DI KANTOR WALI NAGARI KATIAGAN KABUPATEN PASAMAN BARAT - Divia Prestika; Darul Ilmi (Jurnal Komunikasi, 2024)
The purpose of this study was to find out how the head of the service section communicates in public services at the Wali Nagari Katiagan Office. This type of research uses qualitative research which aims to describe the condition or status of phenomena in certain situations including relationships, activities, attitudes, views, and the occurrence of the phenomenon. Data collection was carried out by making observations (observations), interviews, documentation, and looking for research results in the field. The results of the study indicate that the strategy carried out by the service section head is directly or indirectly carried out by the service section head and indirectly through cadres or the Nagari Katiagan apparatus. In the process of conveying information by the head of the service section, the communication strategy applied by the service section head and other nagari officials at the Wali Nagari office is in accordance with the applicable procedures. assessment of the purpose of communication messages and the selection of communication media. The communication strategy effort carried out by the head of this public service section is for the welfare of the community from various programs that exist by the regional government